2022
DOI: 10.1111/gfs.12567
|View full text |Cite
|
Sign up to set email alerts
|

The hunt for the “holy grail”: Condensed tannins in the perennial forage legume white clover (Trifolium repens L.)

Abstract: Forage legumes such as white and red clover improve the nutritional quality of grazed pasture but can cause bloat. Their rapid fermentation in the rumen also contributes to environmental issues through higher methane emissions and urinary nitrogen losses. Condensed tannins are known to reduce urinary nitrogen and methane production from grazing animals, reduce bloat, reduce internal parasite burden, and improve animal productivity. Several forage legumes including birdsfoot trefoil and sainfoin do have good le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Although, oral sensitivity in ruminant species is not well documented, this process can lead to a decrease in preference and eventually a reduction of forage consumption by some livestock species ( Lamy et al., 2011 ). Moreover, the two most cultivated forage legumes, which happen to be low in tannins, white clover and lucerne, have been related with bloat 1 , a common digestive disorder in ruminants that causes damage to gut function ( Caradus et al., 2022 ). On the positive side, legume species presenting high levels of tannin can inhibit the activity of rumen microorganisms and biofilm development, and slowing initial rates of digestion which is a distinguishing bloat-causing feature ( Wang et al., 2012 ).…”
Section: Soil- and Gut Microbes And Functional Diversity Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, oral sensitivity in ruminant species is not well documented, this process can lead to a decrease in preference and eventually a reduction of forage consumption by some livestock species ( Lamy et al., 2011 ). Moreover, the two most cultivated forage legumes, which happen to be low in tannins, white clover and lucerne, have been related with bloat 1 , a common digestive disorder in ruminants that causes damage to gut function ( Caradus et al., 2022 ). On the positive side, legume species presenting high levels of tannin can inhibit the activity of rumen microorganisms and biofilm development, and slowing initial rates of digestion which is a distinguishing bloat-causing feature ( Wang et al., 2012 ).…”
Section: Soil- and Gut Microbes And Functional Diversity Conceptmentioning
confidence: 99%
“…Furthermore, tannins have the ability to reduce the negative impacts of gut parasites, such as for example gastrointestinal nematodes, by inhibiting the activity of key parasite enzymes ( Mueller-Harvey et al., 2019 ). Legume tannins can also reduce methane emissions in agricultural systems directly or indirectly, by either inhibiting gut methanogens (methane producers) or/and protozoal (generates intermediates used by methanogens) populations ( Ku-Vera et al., 2020 ; Caradus et al., 2022 ). Consequently, the ‘anti-nutritional’ view of phytochemicals (as is the case for tannins) is shifting to the point where they are now often considered beneficial for ecological and physiological wellbeing - reducing GHGs emissions and the impacts of climate change, and protecting ruminant health, when consumed in adequate amounts ( Singh and Bhat, 2001 ).…”
Section: Soil- and Gut Microbes And Functional Diversity Conceptmentioning
confidence: 99%
“…A recent advance, using a molecular biology approach, has identified a transcription factor or master switch that can 'turn on' the condensed tannin pathway present in white clover leaves, and with the appropriate promoters allows biologically significant levels of condensed tannin expression in leaf tissue [148,158,159]. In vitro tests have demonstrated that the condensed tannins produced in white clover leaves can bind to protein at pH 6.5, as found in the rumen, and then release them at pH 2.0, the pH in the abomasum This suggests that protein protection in the rumen is possible, and that when released in the acidic abomasum, these proteins will be digested into essential amino acids for absorption in the small intestine of the animal [160,161]. These studies also demonstrated that these condensed tannins could reduce methane production by up to 15% in the first 6 hours of incubation in rumen fluid under laboratory conditions (Figure 3).…”
Section: Environmental Benefitsmentioning
confidence: 99%
“…Unfortunately, species that are often used in temperate grazing systems, such as perennial ryegrass and white clover produce little or no tannins in leaves. However, this issue contains work of Caradus et al (2022) showing how the transformation of white clover with a transcription factor gene has resulted in expression in white clover leaves of condensed tannins at levels that cause effective protein binding in rumen fluid. Clearly this is a breakthrough as white clover is a major forage legume species, and may result in both reduced methane production in vivo and concentration of urinary nitrogen, leading to improved environmental outcomes.…”
Section: Emission Reductionmentioning
confidence: 99%